2015
DOI: 10.1007/s10616-015-9894-5
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo effects of the low molecular weight fucoidan on the bone osteogenic differentiation properties

Abstract: Osteoporosis has been reported as a hidden death factor in aged people. So far, prevention and treatment therapies for osteoporosis only slow down the progress but do not treat the disease. Fucoidan has been recognized its roles in anti-tumor, anti-inflammatory, anti-coagulant and antiviral activities. To date, low molecular weight (LMW) fucoidan role in bone loss disease has been not determined yet. Therefore, this study aims to figure out potential effects of LMW fucoidan in osteoporosis in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 48 publications
2
43
2
Order By: Relevance
“…This result is consistent with our earlier findings, in which the ≤6 kDa fucoidan shows the highest antibacterial activity [6]. It is believed that sulfated polysaccharides (such as fucoidans) with low molecular weight can easily penetrate cell membranes [19,20]. Thus, molecular weight should be one of critical factors determining the antibacterial activity of sulfated polysaccharides.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with our earlier findings, in which the ≤6 kDa fucoidan shows the highest antibacterial activity [6]. It is believed that sulfated polysaccharides (such as fucoidans) with low molecular weight can easily penetrate cell membranes [19,20]. Thus, molecular weight should be one of critical factors determining the antibacterial activity of sulfated polysaccharides.…”
Section: Discussionsupporting
confidence: 92%
“…However, the dose of 100 mg/kg/d did not improve renal function and even slightly worsened renal histologic change in CKD mice. In animal studies, low-molecular weight fucoidan doses of 100 mg/kg/d or higher are often applied to studies of diseases such as cancers, diabetic retinopathy, renal acute injury, and osteoporosis, and exerts significant protective effects25262728. Our results revealed that the high oligo-fucoidan dose promoted renal function and increased the creatinine clearance rate (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…A recent review studying in vivo bone repair experiments showed that low molecular weight fucoidan obtained from brown seaweed increases bone density and bone ash weight following oral administration in mice. These effects were thought to be directly triggered by the osteogenic effect of fucoidan (Hwang et al, ). For example, Pereira et al () showed that treatment of implanted human adipose‐derived stem cells with fucoidan obtained from brown seaweed significantly increased new bone formation in a mouse model.…”
Section: Discussionmentioning
confidence: 99%